Dynamics of livestock and poultry population in India and Himachal Pradesh:A comparative temporal analysis - DINESH, KRISHANENDER; THAKUR, D; SANKHYAN, V; SUMAN, M (The Indian Journal of Animal Sciences, 2023)
The present study on livestock population dynamics can provide useful insights about growth trends of various species and overall livestock population. Such type of analysis is useful for making sound policy and programme planning in livestock sector. The study is based on the secondary data (1977 to 2019) collected from sources such as different livestock census, basic animal husbandry statistics, statistical outlines of India and Himachal Pradesh. The results revealed that India’s cattle population after attaining a peak of 204.5 million in 1992 remained in the range of 190-200 million during majority of census period. Cattle population in Himachal after attaining peak in 2007 has shown sharp decline in last two censuses. During last two census (2007-19) period, buffalo population’s growth has slowed down in India whereas it showed negative growth rate in Himachal Pradesh. Goat population in India showed promising positive trend in majority of census period but in Himachal Pradesh, growth has slowed down. Sheep population also showed steady growth in majority of census period in India whereas in Himachal Pradesh it has declined in every census. Therefore, growth rate of cattle and buffalo population has either stagnated or slowed down in India. On the contrary, cattle, buffalo, sheep population declined in Himachal Pradesh and goat population witnessed slower growth rate in comparison to entire India. The poultry population in the India and Himachal Pradesh increased at impressive and consistent growth rate.